Pengaruh Keaktifan Berorganisasi Terhadap Prestasi Akademik Mahasiswa Program Studi Pendidikan Ekonomi FKIP UPR - Rinto Alexandro; Windy Utami Putri; Fendy Hariatama (FKIP Universitas Palangka Raya, 2022)
The approach used in this study is a quantitative approach and the method is descriptive. The results obtained from this research is the active organization of students with a very active level has an average GPA 3.60 with the highest GPA 3.81 and the lowest GPA 2.43, with active rate activation has an average GPA of 3.31 with the highest GPA 3.75 and 2.25 lowest GPA, and a moderately active activity has an average GPA of 3.36 with the highest GPA of 3.61 and the lowest GPA of 3.11. This indicates that the level of activity is organized at the very active level of the highest average GPA in comparison of active and moderately active levels. However, active organisational activity at the current level has a lower average GPA than the average active GPA of an organization at a fairly active level. There is a positive and significant influence on the activity of students in organization of UPR Economics Education student academic achievement.